2005
DOI: 10.2460/javma.2005.226.1375
|View full text |Cite
|
Sign up to set email alerts
|

Effect of delayed colostrum collection on colostral IgG concentration in dairy cows

Abstract: Results indicate that early or immediate colostrum collection from dairy cows will maximize colostral IgG concentration. Adjustment of routine dairy farm management procedures may be required to maximize colostrum quality and minimize prevalence of failure of passive transfer in dairy calves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
113
3
18

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(149 citation statements)
references
References 12 publications
(11 reference statements)
15
113
3
18
Order By: Relevance
“…Time interval between calving to milking In agreement with previous international studies (Lomba et al, 1978;Straub and Matthaeus, 1978;Moore et al, 2005;Morin et al, 2010), colostrum IgG concentration was negatively associated with the interval from calving to colostrum collection. Corroborating the results from Straub and Matthaeus (1978), the present study failed to identify a significant difference in IgG concentration for cows milked up to 9 h post-calving, although IgG decreased thereafter.…”
Section: Colostral Weightsupporting
confidence: 91%
See 2 more Smart Citations
“…Time interval between calving to milking In agreement with previous international studies (Lomba et al, 1978;Straub and Matthaeus, 1978;Moore et al, 2005;Morin et al, 2010), colostrum IgG concentration was negatively associated with the interval from calving to colostrum collection. Corroborating the results from Straub and Matthaeus (1978), the present study failed to identify a significant difference in IgG concentration for cows milked up to 9 h post-calving, although IgG decreased thereafter.…”
Section: Colostral Weightsupporting
confidence: 91%
“…As such, while post-parturient secretion by the mammary glands of a fluid with a much lower IgG concentration than that of colostrum contributes to lower colostral IgG with increased time from calving to milking (Morin et al, 2010), the present study does not support the view that dilution alone is responsible. Moore et al (2005) also disputed the dilution hypothesis; reporting that while colostrum collected 6, 10 and 14 h after calving from 13 Holstein cows had significantly lower IgG concentrations than colostrum collected 2 h after calving, there was no significant increase in the weight of the colostrum produced at these times. For this reason they concluded that the observed decrease in colostral IgG concentration was not due to dilution effects and suggested that perhaps colostral immunoglobulins diffuse passively into the cow's systemic circulation.…”
Section: Colostral Weightmentioning
confidence: 99%
See 1 more Smart Citation
“…Colostrum is characterised by its very high concentration of immunoglobulin G (IgG), which is of particular importance to the neonate, whose gut, immediately following parturition, allows the passage of large immunoglobulins, thereby conferring passive immunity (Marnila and Korohnen 2002;Tsioulpas et al 2007;Stelwagen et al 2009). It is essential that the newborn calf receives an adequate supply of colostrum as both the concentration of immunoglobulins and permeability of the gut decrease rapidly over the first 24 h following parturition (Weaver et al 2000;Moore et al 2005). In addition, colostrum intake influences metabolism, endocrine systems and the nutritional state of neonatal calves (Guilloteau et al 1997;Blum and Hammon 2000a, b) and stimulates the development and function of the gastrointestinal tract (Hadorn et al 1997;Guilloteau et al 1997;Buhler et al 1998;Blum and Hammon 2000a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Diversos estudios han mostrado que el calostro de las novillas de primer parto presenta una concentración de Igs considerablemente menor que el de vacas con más lactancias y que a su vez, dicha concentración se incrementa conforme aumenta el número de partos (Moore et al, 2005;Gulliksen et al, 2008;Kehoe et al, 2011). Una razón es que las novillas han sido expuestas a antígenos por menor tiempo que vacas con más lactancias; además, el mecanismo de transporte de Igs hacia la glándula mamaria también puede estar menos desarrollado que el de vacas adultas (Devery y Larson, 1983 Cuadro 2.…”
Section: Número De Parto De La Madreunclassified